2014
DOI: 10.1088/1748-6041/9/3/035011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of scaffold microstructure on chondrogenic differentiation of mesenchymal stem cells

Abstract: Different forms of biomaterials, including microspheres, sponges, hydrogels and nanofibres have been broadly used in cartilage regeneration; however, effects of internal structures of biomaterials on chondrogenesis of mesenchymal stem cells (MSCs) remain largely unexplored. Here we investigated the effect of physical microenvironments of sponges and hydrogels on chondrogenic differentiation of MSCs. MSCs, cultured in these two scaffold systems, were induced with TGF-β 3 in chondrogeneic differentiation medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Several studies have been reported on the differentiation potential of hMSCs when cultured on 3D scaffolds with or without the addition of soluble factors. 40,41 However, as far as we know, there is limited knowledge available on the stability of the differentiated phenotype after in vitro culture of hMSC on such 3D scaffolds. In many tissue engineering applications, scaffolds cultured in vitro with hMSCs ultimately have to be implanted in a defect site.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been reported on the differentiation potential of hMSCs when cultured on 3D scaffolds with or without the addition of soluble factors. 40,41 However, as far as we know, there is limited knowledge available on the stability of the differentiated phenotype after in vitro culture of hMSC on such 3D scaffolds. In many tissue engineering applications, scaffolds cultured in vitro with hMSCs ultimately have to be implanted in a defect site.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cell‐laden chitosan‐based hydrogel therapy is widely used in cartilage repair. Studies proved that the implanted cells could replace the cartilage defects and induce the cartilage regeneration . The reason may be attributed to the hydrogel environment, which can induce chondrogenesis by preserving cartilage extracellular signaling …”
Section: Multiple Applicationsmentioning
confidence: 99%
“…Chondrogenesis is initiated by cell condensation during embryonic development, before the mesenchymal stem cells differentiate into multiple lineages, such as articular, growth plate, intervertebral disc chondrocytes or endochondral ossification [some of the cells survive and transform into osteoblasts (Zhang et al, 2014)]. For years, mesoderm was thought to be the origin of MSCs; however, new evidence indicates that the neuroepithelium, including the neural crest, may also be an early origin of MSCs (Morikawa et al, 2009;Takashima et al, 2007).…”
Section: Chondrogenic Differentiation Into Articular Chondrocytesmentioning
confidence: 99%
“…Biomaterials can facilitate chondrogenesis in multiple ways, including mechanical support, surface topography and stiffness, chemical modification and bioactivity (Bian et al, 2013;Lutolf et al, 2009;Wise et al, 2009;Zhang et al, 2014). Co-cultures of chondrocytes and MSCs enhance chondrogenesis due to the trophic role of MSCs (MSCs secrete a variety of cytokines and growth factors that have both paracrine and autocrine activities), which stimulate chondrocyte proliferation and matrix production.…”
Section: Physical Chemical and Biological Factorsmentioning
confidence: 99%